A função social da propriedade imóvel sob a égide da constituição federal e sua efetividade no processo - Abib, Paulo Abiguenem (2005)
This present study from social role from property aim at bring, in the light of from the devices constitutional, of the Civil Code and Statute from City, only one best application you gave principal into the plane she sues. The property always constituted a constant focus of social and economic tensions, destabilizing legal relationships, causing incited conflicts between the people and, these and the State, at last, it has forts repercussions in all the social spheres. The effectiveness you gave principal is of special importance and relevance on conjuncture social actual. The effectiveness you gave principal is of special importance and relevance on conjuncture social actual. The Right always looked for to create instruments and ways that could defend it and pacify it, in the direction to surpass the violent controversies that blow up to its around. Is necessary and urgent operational the beginning constitutional from function from property for your application on the demands of the Justice, principally on the actions of claim of the ownership, of prescription, of expropriation and relative to the half environment. The wars of earth, the violence current from bad distribution from property, the outcry by agrarian reform coming from M.S.T., on the they drive to a deep reflection about to modernize of the secular institute from property, what is being magazine and rethink, no more with a right absolute. The vision individualist is being overcome for new concept of property linked the greeting from a social role. Modernly, an objective is identified that the partner-economic pressures had produced for the legal operator: to accomplish and to materialize the social function of the property. A finished concept will not be presented here and clearly the one that is the social function of the property and nor if it has such pretension in this work. What if it looks for is to offer a starting point of which can be built a new dogmatic conception for the right of property and its social function. About to as many, the survey adopting the method of approach acquainted. The method used was the hypothetical-deductive, owing to what the beginning from social role from property if coated of all a dynamic from reality social what if structure on norm judicial as many constitutional regarding infra constitutional. Such, the end you gave intense and please I study, I hope be able add up, stored the limitations, about to the development from effective application into the I sue from social role from property.